COVID-19 and employees' mental health: stressors, moderators and agenda for organizational actions [version 1; peer review: 2 approved] - Salima Hamouche (Emerald Publishing, 2020)
Background: This paper examines the impact of coronavirus COVID-19 outbreak on employees' mental health, specifically psychological distress and depression. It aims at identifying the main stressors during and post COVID-19, examining the main moderating factors which may mitigate or aggravate the impact of COVID-19 on employees' mental health and finally to suggest recommendations from a human resource management perspective to mitigate COVID-19's impact on employees' mental health. Methods: This paper is a literature review. The search for articles was made in Google scholar, Web of Science and Semantic scholar. We used a combination of terms related to coronavirus OR COVID-19, workplace and mental health. Due to the paucity of studies on the COVID-19 impact on employees' mental health, we had to draw on studies on recent epidemics. Results: The identified literature reports a negative impact of COVID-19 on individual's mental health. Stressors include perception of safety, threat and risk of contagion, infobesity versus the unknown, quarantine and confinement, stigma and social exclusion as well as financial loss and job insecurity. Furthermore, three dimensions of moderating factors have been identified: organizational, institutional and individual factors. In addition, a list of recommendations has been presented to mitigate the impact of COVID-19 on the employee's mental health, during and after the outbreak, from a human resource management perspective. Conclusions: Coronavirus is new and is in a rapid progress while writing this paper. Most of current research are biomedical focusing on individuals' physical health. In this context, mental health issues seem overlooked. This paper helps to broaden the scope of research on workplace mental health, by examining the impact of a complex new pandemic: COVID-19 on employees' mental health, from social sciences perceptive, mobilizing psychology and human resource management.